2019
DOI: 10.1177/0954411919831326
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrodynamic insole on foot kinematics in individuals with flexible flatfoot: Case series using a single-subject design

Abstract: The medial longitudinal arch of the foot is a dynamic structure while walking. The mobility of this structure in people with flexible flatfoot is partially or completely absent. The aim of this study was to investigate the efficacy of an insole that was designed to retrieve the medial longitudinal arch mobility in people with flatfoot. The study was a case series using a single-subject design. This single-subject design study was based on three subjects with flexible flatfoot. This study was designed in two ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…However, the insole presented in this research is prefabricated and ready to be delivered to patients and healthy people. Another characteristic of the insole with universal fluid layer is that it can be suitable for those with flat foot in accordance with the research by Barati et al, 25 due to possessing fluid displacement ability.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, the insole presented in this research is prefabricated and ready to be delivered to patients and healthy people. Another characteristic of the insole with universal fluid layer is that it can be suitable for those with flat foot in accordance with the research by Barati et al, 25 due to possessing fluid displacement ability.…”
Section: Discussionsupporting
confidence: 80%
“…In examining medical insoles, two views on improving the design of insole geometry and improving its material can be evaluated based on experimental test methods [15][16][17] and numerical analysis. [18][19][20] Various medical insoles have been developed based on these two views, including custom-made medical insoles, 21 smart medical insoles, [22][23][24] hydrodynamic medical insoles, 25 Rockertype insoles, 26 multi-plug insoles, 27 shock absorbent medical insoles, 28 vibrating medical insoles, 29 shear reducing insoles, 30 and balance enhancer insoles. 31 Previous studies have shown that if the insole geometry is according to the plantar geometry (custom-made insoles), the person feels more comfortable, and this type of insoles reduces the pressure more considerably than flat insoles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By optimizing the traditional support structure, it can be more suitable for the patient’s plantar structure, thereby reducing damage and improving comfort [10,11]. However, there are currently few studies on customized insoles for patients with flatfoot symptoms, and the number of cases is small [12,13]. Researchers have overlooked the negative effects of inappropriate traditional insoles on patients with flatfoot deformity.…”
Section: Introductionmentioning
confidence: 99%